Combined DaT imaging and olfactory testing for differentiating parkinsonian disorders. Issue 11 (22nd April 2014) - Borghammer, P.; Knudsen, K.; Østergaard, K.; Danielsen, E. H.; Pavese, N.; Arveschoug, A.; Bluhme, H.; Bode, M.; Morsing, A.
Summary: Objective: Dopamine transporter (DaT) imaging with single photon emission computed tomography (SPECT) detects loss of striatal dopaminergic innervation with very high sensitivity. It cannot readily distinguish idiopathic Parkinson's disease (iPD) and dementia with Lewy bodies (DLB) from atypical disorders (aPD). However, most iPD/DLB patients are hyposmic, whereas the majority of aPD patients were reported to have intact olfaction. For this reason, we conducted a longitudinal follow‐up study to investigate the power of combined DaT imaging and olfactory testing to predict the final diagnosis of the patients. Materials and methods: A total of 129 patients received [123I]FP‐CIT SPECT and olfactory testing at baseline assessment. Clinical follow‐up 30 ± 12 months later was the diagnostic standard of truth. A normative dataset of 24 healthy controls was used for comparison. Results: Baseline DaT imaging predicted a dopamine‐deficient diagnosis with 98% sensitivity and 98% specificity. The combined DaT/olfactory testing correctly classified 91% of patients as iPD/DLB (PPV 91%). The PPV rose to 97% or greater in anosmic patients. In contrast, only 45% of aPD patients were categorised correctly by combined DaT/olfactory testing – mainly because of the presence of normosmic iPD patients. Conclusions: In patients with an abnormal DaT SPECT, hyposmia yields an a posteriori likelihood of iPD/DLB of > 90%. In contrast, a finding of normosmia only increases the a posteriori likelihood of aPD to approximately the 50%.